A double endocrine-disrupting effect of PFAS on intra- and extra-thyroid targets: inhibition of iodide uptake and interference with MCT8-mediated T3 transport in vitro - Eleonora Ferrarini; Giuseppina De Marco; Francesca Coperchini; Patrizia Agretti; Alessia Greco; Elena Franchi; Flavia Magri; Luisa Pignata; Valentina Vitelli; Alessandro Saba; Mario Rotondi; Massimo Tonacchera (Environmental Pollution, 2026)

The influence of NaCl on pea proteins based emulgels: From microstructure to macrostructure - Francesca Duggan; Emanuele Greco; Marcello Gigliotti; Eleonora Carini; Francesca Bot (Food Structure, 2026)

Journal of neurovirology - Antonio Mastroianni; Simone Malagò; Valeria Vangeli; Giuliana Guadagnino; Luciana Chidichimo; Maria Vittoria Mauro; Francesca Greco; Robert Tenuta; Lavinia Berardelli; Antonio Mori; Sonia Greco; Concetta Castilletti (Journal of NeuroVirology, 2026)

Searching for New Possible Peripheral Biomarkers of Cognitive Decline in Down Syndrome: The Role of IL-18 Pathway and its Interaction with TGF-β1 and TNF-α - Margherita Grasso; Annamaria Fidilio; Francesca L’Episcopo; Marilena Recupero; Concetta Barone; Marta Lovino; Silvia Alboni; Maria Giulia Bacalini; Giuseppe Caruso; Donatella Greco; Serafino Buono; Rafael De La Torre; et al. (NeuroMolecular Medicine, 2026)

Serum Vitamin E Levels in Multiple Sclerosis: Association with Diagnosis, Cognitive Function, Disability, and Depressive Symptoms - Francesco Bruno; Patrizia Spadafora; Mario Luca Cuconati; Antonio Qualtieri; Ida Veltri; Selene De Benedittis; Beatrice Maria Greco; Annamaria Cerantonio; Luigi Citrigno; Gemma Di Palma; Olivier Gallo; Alberto Montesanto; et al. (Molecular Neurobiology, 2026)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the central nervous system and the most common neurodegenerative disease in young adults, characterized by motor, sensory, visual, and cognitive impairments. Vitamin E (α-Tocopherol), a fat-soluble antioxidant, may influence cognitive function, disability, and mood in MS. One hundred eighty-four Italian Caucasian MS patients and ninety-four healthy controls were included. Clinical and demographic variables were recorded, and serum vitamin E levels were measured by HPLC. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), disability with the Expanded Disability Status Scale (EDSS), and depressive symptoms with the Hamilton Depression Rating Scale (HDRS). Logistic and linear regression analyses were performed, adjusting for demographic, MS-related, and metabolic confounders. Bonferroni correction was applied. Discriminative ability for clinical cut-offs (MMSE ≤ 24, EDSS ≥ 6, HDRS ≥ 8) was assessed using receiver operating characteristic (ROC) curves. MS patients had significantly lower serum vitamin E levels compared to controls. Lower vitamin E levels were associated with MS diagnosis. In MS patients, higher vitamin E levels were associated with better cognitive performance and lower disability. All associations remained significant after Bonferroni correction in fully adjusted models. No significant relationship was found between vitamin E levels and depressive symptoms. Vitamin E showed good discriminative ability. Serum vitamin E levels showed significant associations with MS diagnosis, cognitive function, and disability, with good discriminative ability. Longitudinal studies are needed to clarify whether low vitamin E levels influence the risk of developing MS, while randomized controlled trials are warranted to determine whether vitamin E supplementation may provide clinical benefits.

Evaluation of the effects of PFCAs on spheroid thyroid cells in primary culture: Effects on thyroid function-related genes, tumorigenesis and oxidative stress - Francesca Coperchini; Alessia Greco; Elena Franchi; Matteo Limiroli; Laura Croce; Marsida Teliti; Benedetto Calì; Tshering Dorji; Marco Denegri; Flavia Magri; Mario Rotondi (Environmental Toxicology and Pharmacology, 2025)

In vitro study of the UV-filter homosalate effects on rat and human thyroid cells - Francesca Coperchini; Alessia Greco; Marsida Teliti; Marco Denegri; Laura Croce; Benedetto Calì; Maria Gallo; Giovanni Arpa; Spyridon Chytiris; Flavia Magri; Mario Rotondi (Environmental Pollution, 2024)

Human Campylobacter spp. infections in Italy - Verena Zerbato; Stefano Di Bella; Riccardo Pol; Roberto Luzzati; Gianfranco Sanson; Simone Ambretti; Stefano Andreoni; Richard Aschbacher; Mariano Bernardo; Alessandra Bielli; Gioconda Brigante; Marina Busetti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Phytochemical characterization and biological activities of Stenomesson miniatum bulb extract, a medicinal plant of the Andes - Mariacaterina Lianza; Carmela Fimognari; Jean-Marc Nuzillard; Ferruccio Poli; Jean-Hugues Renault; Francesca Bonvicini; Giulia Greco; Eleonora Turrini (Plant Biosystems, 2024)

Reducing marine litter pollution from anchored fish aggregating devices: Sicilian good practices and the legislative paradox - Francesca De Domenico; Cristina Pedà; Claudio Berti; Pierpaolo Consoli; Francesco Longo; Silvestro Greco; Teresa Romeo (Marine Policy, 2023)

Temporal lobe atrophy as a potential predictor of functional outcome in older adults with acute ischemic stroke - Fabrizio Sallustio; Alfredo Paolo Mascolo; Federico Marrama; Federica D’Agostino; Marco Proietti; Laura Greco; Francesca Di Giuliano; Fana Alemseged; Roberto Gandini; Alessandro Martorana; Marina Diomedi; Giacomo Koch (Acta Neurologica Belgica, 2023)

PFOA, PFHxA and C6O4 differently modulate the expression of CXCL8 in normal thyroid cells and in thyroid cancer cell lines - Francesca Coperchini; Giuseppina De Marco; Laura Croce; Marco Denegri; Alessia Greco; Flavia Magri; Massimo Tonacchera; Marcello Imbriani; Mario Rotondi; Luca Chiovato (Environmental Science and Pollution Research, 2023)

In vitro study of glyphosate effects on thyroid cells - Francesca Coperchini; Alessia Greco; Laura Croce; Marco Denegri; Flavia Magri; Mario Rotondi; Luca Chiovato (Environmental Pollution, 2023)

Gene Expression Profiling of Trematomus bernacchii in Response to Thermal and Stabling Stress - Samuele Greco; Anastasia Serena Gaetano; Gael Furlanis; Francesca Capanni; Chiara Manfrin; Piero Giulio Giulianini; Gianfranco Santovito; Paolo Edomi; Alberto Pallavicini; Marco Gerdol (Fishes, 2022)
The Antarctic continent is one of the most pristine environments on planet Earth, yet one of the most fragile and susceptible to the effects of the ongoing climate change. The overwhelming majority of the components of Antarctic marine trophic chain are stenotherm organisms, highly adapted to the extreme, but extremely stable, freezing temperatures of the Antarctic ocean, which have not changed significantly during the past fifteen million years. Notothenioid fishes are the most abundant representatives of ichthyofauna at these latitudes, being ubiquitously found in coastal areas across the entire continent. While different Antarctic fish species have been previously subjected to studies aimed at defining their range of thermal tolerance, or at studying the response to acute thermal stress, just a handful of authors have investigated the effects of the exposure to a moderate increase of temperature, falling within the expected forecasts for the next few decades in some areas of the Antarctica. Here, the emerald rockcod Trematomus bernacchii was used as a model species to investigate the effects of a 20-day long exposure to a +1.5 °C increase in the brain, gills and skeletal muscle, using a RNA-sequencing approach. In parallel, the experimental design also allowed for assessing the impact of stabling (including acclimation, the handling of fishes and their confinement in tanks during the experimental phase) on gene expression profiling. The results of this study clearly identified the brain as the most susceptible tissue to heat stress, with evidence of a time-dependent response dominated by an alteration of immune response, protein synthesis and folding, and energy metabolism-related genes. While the gills displayed smaller but still significant alterations, the skeletal muscle was completely unaffected by the experimental conditions. The stabling conditions also had an important impact on gene expression profiles in the brain, suggesting the presence of significant alterations of the fish nervous system, possibly due to the confinement to tanks with limited water volume and of the restricted possibility of movement. Besides providing novel insights in the molecular mechanisms underlying thermal stress in notothenioids, these findings suggest that more attention should be dedicated to an improved design of the experiments carried out on Antarctic organism, due to their extreme susceptibility to the slightest environmental alterations.

Morpho-molecular characterization of Ditylenchus gigas and D. oncogenus parasitizing broad bean, Vicia faba, in Algeria - Ines Saadi; Francesca De Luca; Elena Fanelli; Alberto Troccoli; Nicola Greco; Halima Benbouza (European Journal of Plant Pathology, 2019)

Autoimmune vertigo: an update on vestibular disorders associated with autoimmune mechanisms - Francesca Yoshie Russo; Massimo Ralli; Daniele De Seta; Patrizia Mancini; Alessandro Lambiase; Marco Artico; Marco de Vincentiis; Antonio Greco (Immunologic Research, 2018)

Correction to: Sequence variation in ribosomal DNA and in the nuclear hsp90 gene of Pratylenchus penetrans (Nematoda: Pratylenchidae) populations and phylogenetic analysis - Elena Fanelli; Alberto Troccoli; Francesco Capriglia; Giuseppe Lucarelli; Nicola Vovlas; Nicola Greco; Francesca De Luca (European Journal of Plant Pathology, 2018)

Sequence variation in ribosomal DNA and in the nuclear hsp90 gene of Pratylenchus penetrans (Nematoda: Pratylenchidae) populations and phylogenetic analysis - Elena Fanelli; Alberto Troccoli; Francesco Capriglia; Giuseppe Lucarelli; Nicola Vovlas; Nicola Greco; Francesca De Luca (European Journal of Plant Pathology, 2018)

Update on Novel CCM Gene Mutations in Patients with Cerebral Cavernous Malformations - Concetta Scimone; Placido Bramanti; Concetta Alafaci; Francesca Granata; Francesco Piva; Carmela Rinaldi; Luigi Donato; Federica Greco; Antonina Sidoti; Rosalia D’Angelo (Journal of Molecular Neuroscience, 2017)

Nickel-Related Intestinal Mucositis in IBS-Like Patients: Laser Doppler Perfusion Imaging and Oral Mucosa Patch Test in Use - Raffaele Borghini; Marta Puzzono; Edoardo Rosato; Marco Di Tola; Mariacatia Marino; Francesca Greco; Antonio Picarelli (Biological Trace Element Research, 2016)

Effect of neurotoxic compounds on ephyrae of Aurelia aurita jellyfish - Elisa Costa; Chiara Gambardella; Veronica Piazza; Giuliano Greco; Silvia Lavorano; Martina Beltrandi; Elisabetta Bongiovanni; Guido Gnone; Marco Faimali; Francesca Garaventa (Hydrobiologia, 2015)

Spatio-temporal regression on compositional covariates: modeling vegetation in a gypsum outcrop - Francesca Bruno; Fedele Greco; Massimo Ventrucci (Environmental and Ecological Statistics, 2015)

Spatial reconstruction of rainfall fields from rain gauge and radar data - Francesca Bruno; Daniela Cocchi; Fedele Greco; Elena Scardovi (Stochastic Environmental Research and Risk Assessment, 2014)

aSi-EPID transit signal calibration for dynamic beams: a needful step for the IMRT in vivo dosimetry - Francesca Greco; Angelo Piermattei; Luigi Azario; Lorenzo Placidi; Savino Cilla; Rocchina Caivano; Vincenzo Fusco; Andrea Fidanzio (Medical & Biological Engineering & Computing, 2013)

Terpenes from the Red Alga Sphaerococcus coronopifolius Inhibit the Settlement of Barnacles - Veronica Piazza; Vassilios Roussis; Francesca Garaventa; Giuliano Greco; Vangelis Smyrniotopoulos; Constantinos Vagias; Marco Faimali (Marine Biotechnology, 2011)

A generalized calibration procedure for in vivo transit dosimetry using siemens electronic portal imaging devices - Andrea Fidanzio; Francesca Greco; Laura Gargiulo; Savino Cilla; Domenico Sabatino; Massimo Cappiello; Cinzia Di Felice; Elisabetta Di Castro; Luigi Azario; Mariateresa Russo; Luciano Pompei; Guido D’Onofrio; et al. (Medical & Biological Engineering & Computing, 2011)

Dose-guided radiotherapy for lung tumors - Angelo Piermattei; Andrea Fidanzio; Savino Cilla; Francesca Greco; Luigi Azario; Domenico Sabatino; Mattia Grusio; Mariella Cozzolino; Vincenzo Fusco (Medical & Biological Engineering & Computing, 2010)

In patient dose reconstruction using a cine acquisition for dynamic arc radiation therapy - Angelo Piermattei; Andrea Fidanzio; Luigi Azario; Francesca Greco; Alessandra Mameli; Savino Cilla; Luca Grimaldi; Guido D’Onofrio; Boris Giuseppe Augelli; Gerardina Stimato; Diego Gaudino; Sara Ramella; et al. (Medical & Biological Engineering & Computing, 2009)

Daily variations of Urticaceae pollen count and influence of meteoclimatic parameters in East Perugia during 1989 - Marco Fornaciari; Emma Bricchi; Francesca Greco; Daniela Fascini; Claudia Giannoni; Giuseppe Frenguelli; Bruno Romano (Aerobiologia, 1992)

Fluctuations of grass pollen content in the atmosphere of East Perugia and meteorological correlations (year 1989) - Emma Bricchi; Marco Fornaciari; Claudia Giannoni; Francesca Greco; Daniela Fascini; Giuseppe Frenguelli; Gianfranco Mincigrucci; Bruno Romano (Aerobiologia, 1992)